Controlled drinking—non‐abstinent versus abstinent treatment goals in alcohol use disorder: a systematic review, meta‐analysis and meta‐regression. (14th December 2020) - Henssler, Jonathan; Müller, Martin; Carreira, Helena; Bschor, Tom; Heinz, Andreas; Baethge, Christopher
Abstract: Background and Aims: The proportion of untreated patients with alcohol use disorder (AUD) exceeds that of any other mental health disorder, and treatment alternatives are needed. A widely discussed strategy is to depart from the abstinence paradigm as part of controlled drinking approaches. This first systematic review with meta‐analysis aims to assess the efficacy of non‐abstinent treatment strategies compared with abstinence‐based strategies. Methods: CENTRAL, PubMed, PsycINFO and Embase databases were searched until February 2019 for controlled (randomized and non‐randomized) clinical trials (RCTs and non‐RCTs) among adult AUD populations, including an intervention group aiming at controlled drinking and a control group aiming for abstinence. Following Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) and Cochrane Collaboration guidelines, literature search, data collection and risk of bias assessment were carried out independently by two reviewers [International Prospective Register of Systematic Reviews (PROSPERO), registration no. CRD42019128716]. The primary outcome was the proportion of participants consuming alcohol at or below the recommended threshold. Secondary outcomes were social functioning, drinking reductions, abstinence rates and dropouts. Using random‐effects models, RCTs and non‐RCTs were analyzed separately. Sensitivity and subgroup analyses accounted for methodological rigor, inclusion of goal‐specific treatment, length of follow‐up and AUD severity. Results: Twenty‐two studies (including five RCTs) with 4204 patients were selected. There was no statistically significant difference between both treatment paradigms in RCTs [odds ratio (OR) = 1.32, 95% confidence interval (CI) = 0.51–3.39]. Non‐randomized studies of free goal choice favored abstinence‐orientation (OR = 0.60, 95% CI = 0.40–0.90), unless goal‐specific treatment was provided (OR = 0.79, 95% CI = 0.40–1.56), or in studies of low risk of bias (OR = 0.73, 95% CI = 0.49–1.09) or with long follow‐up (OR = 1.49, 95% CI = 0.78–2.85). Effect sizes were not clearly dependent upon AUD severity. Abstinence‐ and controlled drinking interventions did not clearly differ in their effect on social functioning and drinking reductions. Conclusions: Available evidence does not support abstinence as the only approach in the treatment of alcohol use disorder. Controlled drinking, particularly if supported by specific psychotherapy, appears to be a viable option where an abstinence‐oriented approach is not applicable.